(untitled) (Journal of the College of Basic Education, 2022)
The new complexes of Fe(II), Co(II) and Cu(II) with a multidentate Schiff-base ligand [HL] derived from the condensation reaction of ( 2,6-diformyl-4-methyl-phenol) with (4-phenylthiosemicarbazide) in mole ratios of 1:2. The complexes were synthesized in direct reaction of the corresponding metal chloride with the ligand. (FTIR, UV-Vis,1H.13C NMR, A.A), chloride content, conductance and melting point measurements The data of these measurements suggest octahedral geometry around Fe(II), Co(II) and Cu(II) ions. Biological activity of the ligand and its metal complexes against gram positive bacterial strain Bacillus (G+) and gram negative bacteria Pseudomonase (G-) revealed that the metal complexes become less resistive to the microbial activities as compared to the free ligand.